Monkeypox - review - Aleksandra Amalia Kuchnicka; Katarzyna Kosz; Julia Kuchnicka; Klaudia Remjasz; Natalia Zarankiewicz; Martyna Zielińska; Klaudia Sapuła; Jakub Aleksandrowicz; Wojciech Siedlecki (Kazimierz Wielki University, 2022)
Introduction and purpose:  This review aims to analyze the current information about monkeypox and the virus which causes the disease.  Material and method: This review was based on articles collected in PubMed and published in the years 2012-2022 The research was done by looking through keywords as follows: "monkeypox"; "zoonosis";"tecovirimat" Results: The selected studies have demonstrated that the monkeypox virus is a high-danger pathogen that causes a disease important to public health. More research on this topic has to be done to prevent and better comprehend the potential threat.  Conclusions:  According to the cited research, public health systems should be aware of practical methods to reduce the risk of monkeypox spreading. It is crucial to monitor the spreading of the monkeypox disease and create effective preparation. Moreover, governments should develop strategies to prevent their population.